Семантико-синтаксична та лексична специфіка вокатива в ідіолекті Лесі Українки - Городенська, К. (Культура слова, 2021)
Статтю присвячено з’ясуванню семантико-синтаксичних
функцій вокатива, досить поширеного в поетичному ідіолекті Лесі Українки. Обґрунтовано його граматичну специфіку –
переважне вживання в ліричних поезіях із двома вторинними
семантико-синтаксичними функціями: ототожнювальною і
семантичного акцентування адресата, якому про щось повідомляють, та обмеженіше вживання кличного із первинною
семантико-синтаксичною функцією адресата – суб’єкта потенційної дії (носія потенційного стану). Відзначено використання персоніфікованих назв неістот та іменників середнього
роду й іменників у формі множини в позиціях звертання із цими
семантико-синтаксичними функціями вокатива. Простежено особливості лексичного наповнення кличного відмінка,
констатовано органічне використання слів із народного етикету. The article is devoted to elucidating the semantic and syntactic
functions of the vocative, which is quite common in the poetic idiolect
of Lesya Ukrainka. Its grammatical specificity is substantiated –
the predominant use in lyrical poetry with two secondary semanticsyntactic
functions: identification and semantic accentuation of the
addressee to whom something is reported, and more limited use
of the exclamatory with the primary semantic-syntactic function of
the addressee - the subject of potential action). The function of the
vocative identifier is traced mainly by the names of non-beings, and
the function of semantic accentuation of the addressee – mostly by
the names of persons who are informed about something but do
not motivate them to action, and occasionally – by the names of
non-beings. The parameters of the use of personalized names of
masculine and feminine objects and nouns of the middle gender
and nouns in the plural form in the positions of treatment with
these semantic-syntactic functions of the vocative are noted. The
well-known address in the form of the middle genus is a word
that constitutes the lexical and grammatical specificity of Lesya
Ukrainka’s poetic idiolect.
Peculiarities of lexical filling of the accusative case are traced,
the predominant and organic use of words from the vernacular in its
function is stated. The poetess widely used the well-known in folk
etiquette indefinite noun with the collective meaning of brothers
and more limitedly – the indefinite noun gentlemen. A notable
feature of the lexical range of the vocative is the predominant use
of such etiquette words as sir, kind sir, noble lord, friend, heaven (as
a tender address to a man younger than age), brother (as a friendly
address to a man or a loved one, friend), good people and others that
are inherent in the communication of ordinary people.